2015
DOI: 10.1002/stem.1941
|View full text |Cite
|
Sign up to set email alerts
|

Prospectively Isolated Human Bone Marrow Cell-Derived MSCs Support Primitive Human CD34-Negative Hematopoietic Stem Cells

Abstract: Hematopoietic stem cells (HSCs) are maintained in a specialized bone marrow (BM) niche, which consists of osteoblasts, endothelial cells, and a variety of mesenchymal stem/stromal cells (MSCs).However, precisely what types of MSCs support human HSCs in the BM remain to be elucidated because of their heterogeneity. In this study, we succeeded in prospectively isolating/establishing three types of MSCs from human BM-derived lineage-and CD45-negative cells, according to their cell surface expression of CD271 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
53
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(65 citation statements)
references
References 50 publications
11
53
0
Order By: Relevance
“…Recent studies have shown that phenotypically defined fresh human BM MSC subpopulations (eg CD271 + CD140a low/− or CD271 +/− SSEA-4 − ) can support in coculture the growth repopulating potential of human HSC. 40,41 Herein, we favoured the use of culturederived BM MSC to study the correlation between osteogenic differentiation and maturation on the capacity of the feeder cells to support haematopoiesis. Our study demonstrates that the capacity of OCM to promote the growth of CB CD34 + cells and progenitors (CFC, LTC-IC)…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have shown that phenotypically defined fresh human BM MSC subpopulations (eg CD271 + CD140a low/− or CD271 +/− SSEA-4 − ) can support in coculture the growth repopulating potential of human HSC. 40,41 Herein, we favoured the use of culturederived BM MSC to study the correlation between osteogenic differentiation and maturation on the capacity of the feeder cells to support haematopoiesis. Our study demonstrates that the capacity of OCM to promote the growth of CB CD34 + cells and progenitors (CFC, LTC-IC)…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the various subtypes of MSCs that make up the BM niche (illustrated in Fig. 3) have been mainly identified from rodent studies, and it is yet not known if similar cells exist in the human BM; although several recent reports have shown that the human BM niche contains nestin-positive MSCs (Crisan et al., 2008, Matsuoka et al., 2015, Pacini and Petrini, 2014, Schajnovitz et al., 2011). These data corroborate our own published results which demonstrate that around 50% of purified BM-MSC express nestin immunoreactivity (Johnstone et al., 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Previous reports have shown that LNGFR is involved in cell death and axonal degeneration in response to injury . Increasing numbers of studies have demonstrated that LNGFR can serve as a cell surface marker for mesenchymal stem cells (MSCs) and that LNGFR‐positive MSCs present increased potential for osteogenesis . In this study, EMSCs were isolated from embryonic facial processes and sorted to obtain LNGFR + EMSCs and LNGFR − EMSCs.…”
Section: Introductionmentioning
confidence: 99%
“…12 Increasing numbers of studies have demonstrated that LNGFR can serve as a cell surface marker for mesenchymal stem cells (MSCs) and that LNGFR-positive MSCs present increased potential for osteogenesis. [13][14][15][16][17][18] In this study, EMSCs were isolated from embryonic facial processes and sorted to obtain LNGFR + EMSCs and LNGFR − EMSCs. We further demonstrated that LNGFR + EMSCs had a higher osteogenic capacity and lower SOST levels compared with LNGFR − EMSCs and that SOST negatively regulated the osteogenic differentiation of EMSCs.…”
Section: Introductionmentioning
confidence: 99%